Saúde mental na atenção básica: apoio matricial no município de Santos - Ronchetti, Simone de Sousa Bernardino [UNIFESP] (2017)
The Psychosocial Care Network (RAPS) aims to consolidate an open and community-based model of care. It counts on basic care as one of its support points. Matrix support in Mental Health is one of the strategies that aim to establish this network care and redirect the demands put upon the Psychosocial Care Centers (CAPS), which should prioritize the care of patients with serious and persistent mental disorders. That strategy was implemented in the municipality of Santos as of 2011. Objectives: the general objective was to analyze the matrix support that takes place between a CAP and two primary care units in Santos. Method: the research was accomplished by means of a case study that involved documental analysis and focus groups with community health agents. Data were elaborated according to dialetical hermeneutics. Results: it could be observed that the matrix support is redirecting the municipality’s mental health demands with the change of flow of exclusive care at the CAPS to the care at the RAPS. It is important to emphasize the importance of community health agents in the identification of issues and in the care in mental health, with a proximity to the psychosocial model. Conclusion: Despite the need for training and qualification, the potency of lay people knowledge and acting in mental health care was identified, with the matrix support meetings as a place for continuing health education. Matrix support enables the network care that is necessary for completeness, although an articulation among all RAPS’s points is also required.